Extracellular, Surface, and Intracellular Biomineralization of Bacillus subtilis Daniel-1 Bacteria. Issue 8 (2nd August 2021) - Yan, Huaxiao; Owusu, Daniel Cosmos; Han, Zuozhen; Zhao, Hui; Ji, Bei; Zhao, Yanyang; Tucker, Maurice E.; Zhao, Yanhong
Abstract: Even though biomineralization induced by bacteria has been studied for many years, some unsolved problems are still present in the biomineralization, especially the intracellular biomineralization, which should be further explored. In this study, the Bacillus subtilis Daniel-1 strain was identified by 16S rDNA homology, used to induce calcium carbonate biomineralization at various Mg/Ca molar ratios (0, 2, 4, 6, and 8). The results showed that pH still increased at the decline stage in the bacterial growth process, and could increase to about 8.69, resulting from the influence of carbonic anhydrase activity and ammonia. X-ray diffraction (XRD) results showed that calcite, Mg-rich calcite, and aragonite minerals were induced in the extracellular biomineralization process. The diversified morphologies and the presence of fatty acids, protein, and other organic substances in calcium carbonate analyzed by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) proved the biogenesis of these minerals. The stable carbon isotope values (–19.37‰ to −19.79‰) and oxygen isotope values (–6.37‰ to −8.91‰) presented in this study were relatively negative, also confirmed the biogenesis of the minerals. Magnesium carbonate contents in Mg-rich calcite increased from 8.79% to 25.71% with increasing Mg/Ca ratios. Aragonite could be grown not only in cell surface but also inside the cell by analyzing ultrathin slices of bacteria with HRTEM-EDS-SAED. Aragonite in cell surface was elongated whereas intracellular aragonite was granular. To the best of our knowledge, the intracellular biotic crystalline aragonite has rarely been reported. This study is helpful to further understand the mechanism of carbonate mineral biomineralization, and may also provide useful evidence for further studies on intracellular crystal structures.